Association Between Cigarette Smoking and Diabetic Foot Healing: A Systematic Review and Meta-Analysis. (December 2018) - Fu, Xue-Lei; Ding, Hui; Miao, Wei-Wei; Chen, Hong-Lin
The role of smoking for wound healing in patients with diabetic foot has been unclear. This meta-analysis examined the relationship between cigarette smoking and diabetic foot wound healing. Observational studies for the association between smoking and diabetic foot wound healing of patients were systematically searched through PubMed and Wanfang Data, published up to June 2018. Healing rates of wounds were recognized as outcomes. Meta-analysis models were chosen by heterogeneity. A total of 3388 eligible studies were identified, of which 18 met all our inclusion criteria. In the smoking group, healing rate had an average of 62.1%, ranging from 20.0% to 89.6%; in the nonsmoking group, healing rate had an average of 71.5%, ranging from 40.2% to 93.8%. A significant association was found between smoking and the healing of diabetic foot wounds ( z = 3.08; P = .002), with an odds ratio (OR) of 0.70 (95% CI = 0.56-0.88), based on a random-effects model. Meta-regression analyses indicated that the heterogeneity did not come from publication year ( t = −0.50, P = .622) or overall healing rate ( t = 0.16, P = .872). The leave-one-out sensitivity analysis was robust; sensitivity analysis for pooled estimate of adjusted ORs had an OR of 0.20 (95% CI = 0.07-0.56; z = 3.08; P = .002). Subgroup analysis had an OR of 0.62 (95% CI = 0.41-0.95; z = 2.21; P = .027) in retrospective cohort studies and had an OR of 0.75 (95% CI = 0.57-0.99; z = 2.02; P = .043) in prospective cohort studies. Our meta-analysis indicated that smoking had an overall negative effect on the wound healing of diabetic foot individuals. This study provides evidence for the harm of smoking to diabetic foot and may help reduce the medical and economic burden on poor healing of diabetic foot.